Japan's direct investment to ASEAN countries - Katano, Hikoji; Murakami, Atsushi; Ikemoto, Kiyoshi (Kobe : Research Institute for Economics & Business Administration, Kobe University, 1978)
This book consists of case studies on Japan's direct investment to the Association of South-East Asian Nations (ASEAN), the purpose of which is to bridge the gap between general and purely theoretical analysis and the practical evolution of the matter.
Bibliography: p. 137.
usc 25/05/18
Loans
Keywords: Investments, Japanese; Economic assistance; International economic relations; Southeast Asia